2022
DOI: 10.1037/xap0000394
|View full text |Cite
|
Sign up to set email alerts
|

Warning weakens retrieval-enhanced suggestibility only when it is given shortly after misinformation: The critical importance of timing.

Abstract: is now a UX researcher at Workiva. Chan and Manley conceived of the research idea, Manley collected and analyzed the data for Experiment 1, O'Donnell collected the data for Experiments 2 and 3 and analyzed the data for all experiments. Chan analyzed the data for all experiments and wrote the manuscript. O'Donnell and Manley provided comments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 106 publications
2
7
0
Order By: Relevance
“…In both experiments, participants exhibited near-chance performance for these items, and accuracy only exceeded chance at the highest level of confidence. This poor confidence-accuracy relationship shows the evidence-contaminating power of misleading suggestions and replicates recent findings that showed that, in the absence of a warning, misinformation can damage both the accuracy of eyewitness memory reports and the diagnosticity of eyewitness confidence (Chan et al, 2022).…”
Section: Applied Implicationssupporting
confidence: 86%
See 1 more Smart Citation
“…In both experiments, participants exhibited near-chance performance for these items, and accuracy only exceeded chance at the highest level of confidence. This poor confidence-accuracy relationship shows the evidence-contaminating power of misleading suggestions and replicates recent findings that showed that, in the absence of a warning, misinformation can damage both the accuracy of eyewitness memory reports and the diagnosticity of eyewitness confidence (Chan et al, 2022).…”
Section: Applied Implicationssupporting
confidence: 86%
“…In contrast, as participants’ confidence rose, so did their recognition accuracy for the neutral items. Therefore, encountering misinformation severely undermined the diagnosticity of eyewitness confidence ( Chan et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…We predicted that warning would operate to reduce both the misinformation and RES effect in Experiment 1, even in a context where the initial test was delayed from the original event, thereby reducing its ability to support original event memory (e.g., Pansky, 2012). In Experiment 2, we predicted that warnings would be ineffective, in a situation where the initial test of memory was delayed replicating the findings by Chan et al (2022). Further, we predicted that while warnings would reduce average confidence found on misleading trials in Experiment 1, it would have no effect on average confidence when delayed by 24 hours (Experiment 2).…”
Section: The Present Studymentioning
confidence: 81%
“…We employed this retention interval to examine the influence of warnings on final test performance in situations where initial retrieval of the original event would be less likely to improve memory for the original event ( e.g., Pansky, 2012) and still exert an influence on learning and incorporating post-event information ( e.g., Chan & Langley, 2011). We also examined average confidence as research has consistently demonstrated that participants are often highly confident in misinformation (Bonham & González-Vallejo, 2009), and warnings may improve the confidence-accuracy relationship (Chan et al, 2022;Higham et al, 2017;Karanian et al, 2020;Thomas et al, 2010).…”
Section: The Present Studymentioning
confidence: 99%
“…To reduce the impact of misinformation, many prominent online platforms, including Twitter, Facebook, and Google, have implemented warning messages whereby misinformation is explicitly labelled [15][16][17]. This proactive approach has been shown to diminish beliefs in misinformation [18,19], though this effect is only partial [20].…”
Section: Introductionmentioning
confidence: 99%